2013
DOI: 10.1097/inf.0b013e3182862ea8
|View full text |Cite
|
Sign up to set email alerts
|

Asthmatic Children Have Increased Specific Anti–Mycoplasma pneumoniae IgM but not IgG or IgE—Values Independent of History of Respiratory Tract Infection

Abstract: Increased specific IgM anti-M. pneumoniae responses may indicate an important role for M. pneumoniae infection in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Following M. pneumoniae infection, the IgM level has been shown to markedly increase in normal children, which usually occurred 7–14 days following infection, peaked in weeks 3–4 and persisted for months (51). M. pneumoniae infection can cause an increase in the level of total IgE in the serum, whereas delayed-type and anaphylactic-type allergic reactions induce asthma as an immediate reaction and delayed-phase reaction or a dual-phase reaction, which induce the IgE-mediated airway inflammation and airway hyper-reactivity (52). However, there is no direct evidence that M. pneumoniae is the direct cause of asthma.…”
Section: Humoral Immune Damagementioning
confidence: 99%
“…Following M. pneumoniae infection, the IgM level has been shown to markedly increase in normal children, which usually occurred 7–14 days following infection, peaked in weeks 3–4 and persisted for months (51). M. pneumoniae infection can cause an increase in the level of total IgE in the serum, whereas delayed-type and anaphylactic-type allergic reactions induce asthma as an immediate reaction and delayed-phase reaction or a dual-phase reaction, which induce the IgE-mediated airway inflammation and airway hyper-reactivity (52). However, there is no direct evidence that M. pneumoniae is the direct cause of asthma.…”
Section: Humoral Immune Damagementioning
confidence: 99%
“…71 In another cross-sectional study, asymptomatic asthmatic patients had higher acquisition rates, as measured by reverse transcriptase-PCR, of M pneumoniae (45%) and Chlamydia pneumoniae (13%), than nonasthmatic persons (9% and 0%, respectively). 72 The potential negative impact of Th2-biased response on immunity has been further demonstrated for leishmaniasis, 73 toxoplasmosis, 74 schistosomiasis, 75 and candidiasis.…”
Section: Effect Of Atopic Conditions On the Risk Of Microbial Infectionsmentioning
confidence: 94%
“…72 The potential negative impact of Th2-biased response on immunity has been further demonstrated for leishmaniasis, 73 toxoplasmosis, 74 schistosomiasis, 75 and candidiasis. 76 If patients with asthma and other atopic conditions have normal IgM responses to exposure to microbial organisms (eg, as evidence for mycoplasma infection 71 ) but suboptimal IgG response as discussed in the mechanism section, these data may suggest some impairment in the immune pathways post-IgM production by B-cells (e.g., impairment in isoclass switching, postswitch defect, or a more rapid waning of humoral immunity).…”
Section: Effect Of Atopic Conditions On the Risk Of Microbial Infectionsmentioning
confidence: 99%
“…2 Previous studies have shown that individuals with asthma have an increased risk of serious and common infections of the respiratory tract, such as invasive pneumococcal diseases, 3,4 Streptococcus pyogenes , 5 Bordetella pertussis , 6 Staphylococcus aureus , 7 otitis media, 7 otitis media, 8 and Mycoplasma pneumoniae. 9 and adaptive immunity, 10 which may partly explain this increased propensity for infection. A recent review has posited that asthma may be more than a just a chronic airway disease as asthma also appears to possess features characteristic of systemic immune dysfunction.…”
Section: Introductionmentioning
confidence: 99%